2023
DOI: 10.1029/2023ja031882
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Electron Flux Dropouts in the Earth's Outer Radiation Belt on Energy and Driving Parameters During Geomagnetic Storms

Man Hua,
Jacob Bortnik,
Donglai Ma

Abstract: Using 5‐year of measurements from Van Allen Probes, we present a survey of the statistical dependence of the Earth's outer radiation belt electron flux dropouts during geomagnetic storms on electron energy and various driving parameters including interplanetary magnetic field Bz, PSW, SYM‐H, and AE. By systematically investigating the dropouts over energies of 1 keV–10 MeV at L‐shells spanning 4.0–6.5, we find that the dropouts are naturally divided into three regions. The dropouts show much higher occurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 89 publications
(137 reference statements)
0
8
0
Order By: Relevance
“…And, magnetospheric compressions can also lead to the anisotropic distributions of ions and electrons, which generate EMIC waves on the dayside (e.g., Anderson and Hamilton, 1993;McCollough et al, 2010;Usanova et al, 2012;Zhang et al, 2016b;Saikin et al, 2016;Xue et al, 2023;Yan et al, 2023) that can cause the loss of relativistic and ultrarelativistic electrons (e.g., Zhang et al, 2016a;Su et al, 2017;Zhu et al, 2020). Hua et al (2023) found that the most significant flux losses of >1 MeV electrons occurred during the strong solar wind dynamic pressure while the flux losses barely occurred during the weak solar wind dynamic pressure. During the second geomagnetic storm of the three continuous geomagnetic storm events in this study, the solar wind dynamic pressures were relatively low or had only an instantaneous enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…And, magnetospheric compressions can also lead to the anisotropic distributions of ions and electrons, which generate EMIC waves on the dayside (e.g., Anderson and Hamilton, 1993;McCollough et al, 2010;Usanova et al, 2012;Zhang et al, 2016b;Saikin et al, 2016;Xue et al, 2023;Yan et al, 2023) that can cause the loss of relativistic and ultrarelativistic electrons (e.g., Zhang et al, 2016a;Su et al, 2017;Zhu et al, 2020). Hua et al (2023) found that the most significant flux losses of >1 MeV electrons occurred during the strong solar wind dynamic pressure while the flux losses barely occurred during the weak solar wind dynamic pressure. During the second geomagnetic storm of the three continuous geomagnetic storm events in this study, the solar wind dynamic pressures were relatively low or had only an instantaneous enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous SVM tutorials are available in the literature (e.g., Burges, 1998;Chang & Lin, 2011;Cortes & Vapnik, 1995;Melgani & Bruzzone, 2004). Considering that the dropout data set is a relatively small data set with tens to hundreds of dropout samples at a given L-shell and energy (Hua et al, 2023), and the time series of various driving parameters will be used as inputs (i.e., a high-dimensional problem), SVM is particularly appealing for dropout predictions.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Recent statistical studies reported the important impact of high solar wind dynamic pressure (P SW ) and southward interplanetary magnetic field (IMF) B z on producing significant relativistic electron dropouts (Gao et al, 2015;Gokani et al, 2022;Hua et al, 2023;Onsager et al, 2007;Yuan & Zong, 2013). Moreover, Hua et al (2023) suggested that dropouts strongly depend on storm (SYM-H index) and substorm (AE index) conditions. The SYM-H index, equivalent to Dst index, measures the ring current intensity near Earth (Wanliss & • We investigate the critical driving factors controlling dropouts by constructing dropout prediction models using Support Vector Machines (SVMs)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations